Chemical, Spectral, Biological, and Toxicological Studies of Some Benzene Derivatives Used in Pharmaceuticals: In Silico Approach - Kabir, Emranul; Noyon, M R O Khan; Alam, Md Rabiul; Nasiruddin, Mr.; Islam, Sajia; Akter, Mahima; Uzzaman, Monir (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
The immune system of humans is impacted by many drugs. Chemicals that have a gender-bending impact on boys, were synthesized, their use spread, and as a consequence, they entered the ecology, the food chain, and eventually ended up in blood or human breast milk. Due to the use of benzene in both industry and medicine, chemicals with benzene rings are among the most problematic. The generation of benzene metabolites that produce superoxide, the phenoxy radical, and benzene-drug binding are only a few of the processes by which benzene and its derivatives cause harm. Benzene metabolites are distinct from chemical metabolites apart from benzene, which is lipophilic in nature and binds to cellular membranes, in that they bind to the intracellular plasma membrane where they produce degenerative alterations. Many diseases are associated with degenerative alterations in the mitochondria that culminate in mitochondrial dysfunction. Herein, twenty benzene derivatives (BDs) have been studied in terms of their biological and physiochemical properties, and the compounds have also been investigated using quantum mechanical computations. Binding affinities and behaviors of all BDs have been investigated using molecular docking and nonbonding interactions on 3D crystal structures of human receptor proteins serum albumin (1AO6), free native cellulase CEL48F (1G9G), and human D-amino acid oxidase mutant (P219L) complexed with benzoate (6KBP). Geometry as well as thermochemical data support the stability of all structures. All derivatives were predicted by ADMET to have improved pharmacokinetic properties and less acute oral toxicity.